Efeito de argilas organofílicas na estrutura e propriedades de nanocompósitos de poli(metacrilato de metila) - Rodrigues, Lourdes Aparecida Ribeiro (2013)
Nacomposites of polymers and lamellar clayminerals, has generated high scientific and technological interest, for having mechanical properties and gas barriers differentiated of polymers and conventional composites. In this work, it was developed nanocomposites by single screw extruder and injection, utilizing commercial raw material, with the goal to investigate the quality of new developed materials. It was evaluated the influence of the content and the kind of clay in the structure and in the nanocomposites properties. It was used regular and elastomeric poly (methyl methacrylate) (Acrigel LEP 100 and Acrigel ECP800) and six montmorillonites (Cloisite 10A, 11B, 15A, 20A, 25A e 30B) at the concentration of 1% e 3% in weight. The nanocomposites were characterized by X-ray diffraction (XRD), thermal gravimetric analysis (TGA), transmission electron microscopy (TEM), colorimetric, optical transparency, flexural and tensile tests, Rockwell hardness and esclerometry. It was founded that is possible to obtain intercalated and exfoliated nanocomposites PMMA/MMT, and the top results was obtained in the materials with 1%in clay weight organophilizated with 2M2HT (Cloisite 15A and 20A) presented intercalate and hybrid morphology (exfoliated and flocullated). The ones that was produced with organophilizated clay with 2MHTL8 (Cloisite 30B) had excellent visual quality, but the majority presented hybrid morphology. In the materials processed with organophilizated clay with MT2ETOH (Cloisite 30B), there were color change and loss of transparency. It occurs improvement in a few mechanical properties, mainly in the materials produced with PMMA elastomeric (Acrigel ECP800), being more significant, the increase in the resistance to stripping in those nanocomposites